Development of Locally Resonant Structures for Sonic Barriers. Issue 3 (September 2014) - Hall, Andrew; Calius, Emilio; Dodd, George; Wester, Eric; Chan, KL
The application of metamaterials or structured material principles to sound insulation has produced a new isolation concept known as locally resonant structures (LRS). LRS combine interacting components specifically arranged to generate localised resonances within the structure. LRS have exceptional sound transmission loss (TL) performance in defined frequency bands, which can be tailored for any desired region of the spectrum. Low frequency noise (below 1 kHz) is where irritating acoustic intrusion frequently occurs but is both challenging and expensive to prevent with conventional solutions, and where the LRS is a potentially compact and relatively lightweight solution. Numerical models based on networks of single-degree of freedom oscillators were used to understand how the components of the LRS can be manipulated to generate a designated TL performance spectrum. Designs with the desired TL characteristics were then modelled using FEA software, and samples were fabricated for testing. This paper will focus on results obtained by testing the LRS samples in an impedance tube adapted for TL experimentation. These results showed that the highest performing network arrangements combined layers of multiple resonators with incremental resonant frequencies to increase system bandwidth. Experimental data for various LRS arrangements shows good correspondence to modelling predictions. Samples yielded systems with attenuation peaks of 80dB over band widths approaching 350 Hz at frequencies well below 1 KHz These results provide insight into the benefits and limitations of complex LRS, and how to use this technology for practical applications.